The effect of temperature and storage time off semen samples on the spermatozoa deoxyribonucleic acid (DNA) fragmentation - Nathalia, Jennifer; Pasaribu, Wanly Syahrizal; Darsini, Ninik; Narulita, Pety; Pramesemara, I. Gusti Ngurah; Mohd Tamrin, Mohd Islahuddin (Sami Publishing Company, 2026)
DNA fragmentation analysis is essential for evaluating sperm DNA integrity, which affects fertilization, embryo development, and pregnancy outcomes. However, many Indonesian laboratories lack access to this testing due to limited availability of commercial kits. This study aimed to assess the effects of storage temperature and duration on sperm DNA fragmentation by comparing fresh semen samples with those stored under various conditions. This post-test-only experimental study was conducted at the Biomedical Laboratory, Faculty of Medicine, Universitas Airlangga, Surabaya, from March to October 2023. Semen samples were collected from ten normozoospermic men aged 20-35 years. The samples were divided into four groups: fresh samples (P1), samples stored in a cool box (7-8 °C) for 3 hours (P2), and samples stored in a freezer at-16 °C for 3 days (P3) and 7 days (P4). DNA fragmentation was assessed using the Sperm Chromatin Dispersion (SCD) method. The Shapiro-Wilk test was used for normality. Depending on data distribution, paired t-tests or Wilcoxon signed-rank tests were applied. No significant differences were found in DNA fragmentation index between fresh and stored samples: P1 vs. P2 (p = 0.257), P1 vs. P3 (p = 0.705), and P1 vs. P4 (p = 0.102), indicating DNA stability. Sperm DNA fragmentation remains stable under the tested storage conditions. Semen samples can be stored at 7-8 °C for 3 hours or frozen at-16 °C for up to 7 days without compromising DNA integrity.